Processing of Fallen Leaves to Produce Ecological Clean Gas - Ashurov Doston Abduraim ogli; Kushnazarov Pulat Islamovich, (European Journal of Life Safety and Stability (2660-9630), 2022)
The possibility of recycling fallen leaves and obtaining biogas from plant raw materials of urban parks is considered. The calorific characteristics of the biogas obtained were quantified and analyzed. The chemical composition of the plant substrate formed as a result of mesophilic fermentation of plant biomass is investigated. The practical application of a plant substrate as a fertilizer has been studied by the example of germination of vegetable seeds. The prospects for further research to optimize the fermentation regime of plant mass during the processing of fallen leaves are analyzed. Obtaining biogas from the fallen leaves of urban parks and squares makes it possible to simultaneously solve energy, environmental, and social issues, both local and more general.